Laparoscopic Cornuostomy: A Conservative Surgical Approach to Interstitial Pregnancy - A Case Report - Vinod Nair; Gunjan Rai; Roshni Abichandani; Abhijeet Kumar; Eshwarya Jessy Kaur (Wolters Kluwer Medknow Publications, 2024)
Interstitial pregnancy accounts for only 2%-4% of all ectopic pregnancies, however, it is associated with higher mortality rates as compared to other ectopic pregnancies, due to the associated risk of uterine rupture, and hemorrhage. A 35-year-old gravida 4 abortion 3 woman reported at the 8th week of gestation for antenatal care with comorbidity of protein C and protein S deficiency and recurrent pregnancy loss with for routine care. She was diagnosed as a case of interstitial pregnancy by transvaginal sonography and magnetic resonance imaging. She was subsequently managed by laparoscopic cornuostomy. Prompt recognition and definitive management are crucial in averting life-threatening hemorrhage due to this rare condition.